Platform Digital Pemesanan Iklan PT Sumatera Ekspres Berbasis Dashboard Analitik dan Notifikasi WhatsApp - Ilham Apriliansah; Muhammad Izman Herdiansyah; Dinny Komalasari; Muhammad Nasir (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
PT. Sumatera Ekspres still relies on manual recording of advertisement bookings and customer data. Therefore, this study aims to design and develop a web-based information system for advertisement booking and customer management that integrates an analytics dashboard with an automatic WhatsApp notification feature. The study employs the Research and Development (R&D) method combined with the Rapid Application Development (RAD) approach, comprising the Requirements Planning, User Design, Construction, and Implementation stages. The system was developed using the Laravel framework, MySQL database, and Fonnte API for WhatsApp integration, and was evaluated using Black Box Testing. The results show that the system successfully digitizes and integrates advertisement booking and customer data management, provides real-time data visualization through a Chart.js-based analytics dashboard, and automatically sends WhatsApp notifications to customers. Black Box Testing of 10 scenarios showed that all scenarios were valid, indicating that the tested features functioned according to their specifications. The integrated platform provides a more structured and centralized approach to managing advertisement and customer data at PT. Sumatera Ekspres.